The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/agronomy11061124
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Lab and the Field: Genome Analysis of Phyllobacterium and Rhizobium Strains and Field Performance on Two Vegetable Crops

Abstract: The legume nodules are a rich source not only of rhizobia but also of endophytic bacteria exhibiting plant growth-promoting mechanisms with potential as plant biostimulants. In this work we analyzed the genomes of Phyllobacterium endophyticum PEPV15 and Rhizobium laguerreae PEPV16 strains, both isolated from Phaseolus vulgaris nodules. In silico analysis showed that the genomes of these two strains contain genes related to N-acyl-homoserine lactone (AHL) and cellulose biosynthesis, involved in quorum sensing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(88 reference statements)
0
7
0
Order By: Relevance
“…Another important nutrient for plant cells is Fe but, despite its abundance on Earth, it is not widely accessible in soils, when it is present in complexes of hydroxides and oxyhydroxides. Different PGPB, such as Pseudomonas, Bacillus, and Phyllobacterium found in this study, possess the ability to synthesise siderophores, Fe-chelating compounds having a high a nity to Fe 3+ and forming complexes that lead to the mobilisation of Fe (reduced to Fe 2+ ), making it bioavailable and absorbable by the plant roots (Shilev 2020;Pérez-Rodriguez et al 2020;Flores-Félix et al 2021). Moreover, it is known that siderophore-producing bacteria play a crucial role not only in growth promotion but also in biocontrol activity, by competing for Fe 3+ with the pathogens in the rhizosphere (Kumar et al 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Another important nutrient for plant cells is Fe but, despite its abundance on Earth, it is not widely accessible in soils, when it is present in complexes of hydroxides and oxyhydroxides. Different PGPB, such as Pseudomonas, Bacillus, and Phyllobacterium found in this study, possess the ability to synthesise siderophores, Fe-chelating compounds having a high a nity to Fe 3+ and forming complexes that lead to the mobilisation of Fe (reduced to Fe 2+ ), making it bioavailable and absorbable by the plant roots (Shilev 2020;Pérez-Rodriguez et al 2020;Flores-Félix et al 2021). Moreover, it is known that siderophore-producing bacteria play a crucial role not only in growth promotion but also in biocontrol activity, by competing for Fe 3+ with the pathogens in the rhizosphere (Kumar et al 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Different PGPB, such as Pseudomonas, Bacillus, and Phyllobacterium found in this study, possess the ability to synthesise siderophores. These Fe-chelating compounds have a high affinity to Fe 3+ and form complexes that lead to Fe-mobilisation (reducing Fe 3+ to Fe 2+ ) and make it bioavailable for plant roots (Shilev 2020;Pérez-Rodriguez et al 2020;Flores-Félix et al 2021). Moreover, it is known that siderophoreproducing bacteria play a crucial role not only in growth promotion but also in biocontrol activity, by competing for Fe 3+ with the pathogens in the rhizosphere (Kumar et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Within the new agricultural technologies, the inoculation of crops with plant growth-promoting bacteria (PGPB) as bio-fertilisers has emerged as a sustainable and environmentally friendly method to improve soil fertility and plant growth, while simultaneously reducing the application of synthetic fertilisers, and maximising the efficiency in the use of resources (Flores-Félix et al 2021;Kumar et al 2022). Moreover, the cost of biological fertilisers can be competitive compared to chemical fertilisers (Lobo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many Rhizobium species have been shown to colonize the rhizosphere of non-leguminous plants and promote their growth and disease resistance, making them an attractive option as biofertilizers for a wide range of crops ( García-Fraile et al, 2012 ; Flores-Félix et al, 2019 ; Kang et al, 2019 ; Kumar et al, 2020 ). For instance, studies have demonstrated the beneficial impact of specific strains such as Rhizobium leguminosarum PETP01 and TVP08 on pepper ( Silva et al, 2014 ), R. laguerreae PEPV40 on spinach ( Jiménez-Gómez et al, 2018 ), and R. leguminosarum PEPV16 on lettuce and carrot ( Flores-Félix et al, 2021 ). Plants inoculated with these strains produced significantly higher numbers of fruits with greater fresh weight, and the fruits reached the maturation stage earlier.…”
Section: Introductionmentioning
confidence: 99%